IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA PELAJARAN AKIDAH AKHLAK DI MTS NEGERI 1 YOGYAKARTA - Hasan Basri (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
Abstract:This study aims to find out how the implementation of the independent learning curriculum is implemented, to find out the obstacles encountered in the implementation of the independent learning curriculum, and to find out how the form of assessment of akidah moral learning is based on the independent curriculum at MTs Negeri 1 Yogyakarta. This research is a field research using descriptive qualitative method. Collecting data in this study using interviews, observation and documentation. The results of this study indicate that: 1) there are four policies in the implementation of the independent learning curriculum, namely the National Examination is replaced by a Minimum Competency Assessment and character survey, the National Standardized School Examination is handed over to schools, the simplification of the Lesson Implementation Plan (RPP) is only one page, and the expansion acceptance of new students. 2) The implementation of the independent learning curriculum in the Aqeedah Akhlak subject is composed of several designs, starting with the introduction, core activities, elaboration, communication and confirmation. and finally the closing. 3) The assessment process for the Aqeedah Akhlak subject at MTs Negeri 1 Yogyakarta carries out several forms of assessment, such as daily assessments in the form of questions or written notes at the end of the semester.